Superhard aggregate grinding material with high bonding strength characteristic and preparation method of superhard aggregate grinding material
Through component design and sintering process optimization, superhard aggregate abrasives with high binding strength were prepared, which solved the problems of abrasive particles crushing and tool applicability of superhard abrasives under high load conditions, and achieved stability under high load The effect of processing and long-life abrasives.
Patent Information
- Application Number
- CN202411329391.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-07
AI Technical Summary
The existing ultrahard abrasive particles break prematurely under high load conditions, resulting in unstable and inefficient processing. In addition, aggregate abrasives are only suitable for resin tools and cannot be used for ceramic tools.
Using component design, brazed metal bonding agent and binder preferred, combined with sintering process optimization, ultra-hard aggregate abrasives with high binding strength characteristics, including ultra-hard abrasive diamond or cubic boron nitride and brazed The metal bonding agent has a ratio of 50 to 85% and 15 to 50%. Abrasives with high bond strength are obtained through mixing, granulation, medium-temperature glue removal and high-temperature sintering.
It realizes the stability of abrasive particles and the long life of abrasive tools under high load conditions. It can be suitable for the preparation of resin and ceramic tools, meets the needs of grinding, cutting, grinding, polishing and honing, and improves processing efficiency and stability. sex.
Smart Images

Figure CN119264872A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a kind of abrasive preparation, abrasive processing (grinding, cutting, grinding, polishing, honing) technology, especially a kind of superhard aggregate abrasive technology with high bonding strength characteristics, specifically a kind of superhard aggregate abrasive with high bonding strength characteristics and its preparation method. Background Art
[0002] In the field of abrasive processing, with the maturity of synthesis technology and the decline of production costs, super-hard abrasives (diamond, cubic boron nitride) are more and more widely used in the field of abrasive processing. During the abrasive processing, the failure forms of super-hard abrasives mainly include passivation, shedding, micro-crushing and macro-crushing caused by edge wear. Under high-load conditions, the abrasive particles of resin abrasive tools are subjected to large tangential forces, and the early shedding of abrasive particles is the main failure form, which shortens the service life of the abrasive tools and makes the processing unstable and inefficient.
[0003] To prevent abrasive grains from falling off prematurely, abrasive grain plating treatment is mainly used. For example, the surface of superhard abrasives is plated with nickel or copper to prepare resin-based superhard material abrasives. Although the working life of resin abrasives is improved, there are two side effects: First, when the copper- or nickel-plated abrasives are exposed, the nickel layer or copper layer on the surface of the abrasives is relatively soft, resulting in a decrease in the processing ability of the abrasive grains; second, the rough surface can easily cause the passivated abrasives to fail to fall off in time, and they need to be trimmed before they can continue to be used. Based on the above situation, Nanjing University of Aeronautics and Astronautics has developed superhard abrasive grains with aluminum oxide or nickel oxide coating on the surface (invention patents ZL201210209689.X and ZL201210210174.1), which have improved the processing ability of abrasive grains and the problem of passivated abrasive grains falling off to a certain extent.
[0004] In order to solve the problem of abrasive passivation caused by abrasive edge wear, granular polycrystalline diamond (or cubic boron nitride) abrasives are used to achieve micro-crushing of abrasives by taking advantage of the weak grain boundaries. However, the polycrystalline abrasives need to be prepared under high temperature and high pressure conditions, and the process is complex and costly. Nanjing University of Aeronautics and Astronautics has developed a self-sharpening sintered abrasive (invention patent ZL201610243158.0), which uses the low-cycle fatigue properties of the ceramic (glass) binder in the sintered abrasive to achieve a certain degree of micro-crushing. It is used in hydrophilic resin bonded abrasives and significantly improves processing stability. However, it was found during use that under high pressure conditions such as grinding and cutting, the abrasive is subjected to a large tangential force, and the abrasive is crushed quickly, which reduces the processing performance of the aggregated diamond abrasive, resulting in instability in the processing process of the hydrophilic resin bonded abrasive and a reduced lifespan. In addition, current aggregate abrasives are only suitable for the preparation of resin-based tools. During the processing, when the aggregate abrasives on the surface of the resin-based tool are worn out, the resin-based surface is eroded, which can expose the aggregate diamonds in the subsurface layer. Since the elastic modulus and fracture strength of the ceramic base are higher than those of the resin base, the holding force on the aggregate abrasive is higher. The aggregate abrasives in the subsurface layer cannot be exposed, resulting in tool failure and cannot be used for ceramic-based tools, making the aggregate abrasives single-purpose. Therefore, it is extremely necessary to develop a superhard aggregate abrasive with high bonding strength characteristics, which can not only meet the needs of conventional grinding, cutting, grinding, polishing and honing tools, but also meet the needs of grinding tools under high load conditions; it can be used not only for the preparation of resin tools but also for the preparation of ceramic tools. Summary of the invention
[0005] The content of the present invention is to address the problems that the existing self-sharpening sintered abrasives are subjected to large tangential forces under relatively high load conditions, resulting in premature breakage of the abrasive particles, leading to unstable processing and low processing efficiency, and the aggregate abrasives are only suitable for single resin tool applications. A superhard aggregate abrasive with high combined strength characteristics that is simple to prepare is invented, and a preparation method thereof is also provided. The present invention obtains a superhard aggregate abrasive with high combined strength characteristics through a series of processes such as component design, optimization of brazing-type metal binders, optimization of adhesives, screening and granulation, and optimization of sintering processes. The superhard aggregate abrasive can be used to prepare resin tools and ceramic tools, and applied to grinding, cutting, grinding, polishing and honing of various workpieces, especially in the field of high-load processing technology.
[0006] One of the technical solutions of the present invention is:
[0007] A superhard aggregate abrasive with high bonding strength characteristics, characterized in that it is composed of superhard abrasive diamond or cubic boron nitride and a brazing type metal binder, the mass percentage of the superhard abrasive diamond or cubic boron nitride is 50-85%, the content of the brazing type metal binder is 15-50% by mass, and the sum of the components is 100%.
[0008] The brazing type metal binder is one or more combinations of copper-based alloy, nickel-based alloy and silver-based alloy, so that the superhard aggregate abrasive grains have high bonding strength and the abrasive grains will not break prematurely under greater pressure.
[0009] The original particle size of the diamond abrasive grains or cubic boron nitride abrasive grains, ie, the primary particle size, is distributed between 1 and 30 μm.
[0010] The brazing type metal binder particle size is -300 mesh.
[0011] The second technical solution of the present invention is:
[0012] A method for preparing a superhard aggregate abrasive having high bonding strength characteristics, characterized in that it comprises the following steps:
[0013] (1) Super-hard abrasive grains and brazing-type metal binders are prepared in proportion and mixed evenly; (2) A binder is added to the above mixed raw materials to prepare granules; (3) The granulated mixture is spread evenly in a crucible, placed in a vacuum furnace, and heated in stages to perform medium-temperature debonding and high-temperature sintering; (4) Screening and grading are performed to obtain super-hard aggregate abrasives with high bonding strength characteristics.
[0014] In step (1), the mixing method is dry mixing, and the mixing time is 0.5 to 12 hours;
[0015] In the step (2), the binder is a mixture of one or more of polyvinyl alcohol, polyvinyl acetate and polyvinyl acetal, and the content thereof is 1% to 15% of the mass of the mixed raw materials.
[0016] In the step (3), the temperature of the medium-temperature degumming is 200-600° C., the degumming time is 0.25-1 hour, and the vacuum degree of the vacuum furnace is controlled to be lower than 133 Pa.
[0017] In the step (3), the sintering temperature varies between 800 and 1000° C. according to the type and proportion of the brazing metal binder, the sintering time is 0.5 to 4 hours, and the vacuum degree of the vacuum furnace is controlled to be lower than 133 Pa.
[0018] In the step (4), the sintered abrasive particles are sieved using a 40-320 mesh sieve.
[0019] The third technical solution of the present invention is:
[0020] A superhard aggregate abrasive with high bonding strength characteristics, characterized in that it is used in the preparation of resin and ceramic superhard abrasive tools, and the superhard abrasive tools include grinding wheels, blades, grinding discs, polishing discs and honing heads used in precision grinding, cutting, grinding, polishing and honing.
[0021] The beneficial effects of the present invention are:
[0022] The present invention obtains a superhard aggregate abrasive with high bonding strength characteristics through a series of processes such as component design, optimization of brazing type metal binder, optimization of adhesive, granulation and optimization of sintering process. The superhard aggregate abrasive can be used to prepare resin tools and ceramic tools, and is applied to grinding, cutting, lapping, polishing and honing of various workpieces, especially in the field of high-load working condition processing technology.
[0023] The resin-based and ceramic superhard abrasive tools prepared from the superhard aggregate abrasive of the present invention can meet the needs of ultra-precision grinding, lapping and polishing processing, solve the problem that the level of ultra-precision tools in my country cannot keep up with the pace of the world, and have completely independent intellectual property rights.
[0024] The superhard aggregate abrasive designed and prepared by the present invention has high-strength bonding characteristics. Under a relatively large load condition, when the abrasive particles are subjected to a large force, the elastic modulus of the binder can be appropriately increased, and the metal binder has a strong holding force on the superhard abrasive particles, and will not easily cause the raw abrasive particles (primary particle size abrasive particles) to fall off from the surface of the superhard aggregate abrasive particles (secondary particle size abrasive particles), thereby making the abrasive tool have a longer service life. The aggregate abrasive with high bonding strength characteristics provided by the present invention can stabilize the processing efficiency under a relatively strong working load and ensure the service life of the abrasive tool. It can be used as abrasive particles to prepare resin (or ceramic) grinding wheels, blades, grinding discs, polishing discs and honing heads, and can be used for processing techniques such as precision grinding, cutting, grinding, polishing and honing. The method provided by the present invention has the advantages of simple process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a stereomicroscope image of the aggregate abrasive grains of the present invention, showing the morphology of the abrasive grains after sintering, where the diamond primary particle size abrasive grains are bonded together by a metal binder to form superhard aggregate secondary particle size abrasive grains.
[0026] Figure 2 This is the SEM image of the ceramic bond aggregate abrasive grains of Comparative Example 1. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0028] Example 1.
[0029] like Figure 1 shown.
[0030] A superhard aggregate abrasive with high bonding strength characteristics is made of 500 grams of 1-10 μm diamond powder and 500 grams of brazing type metal binder copper-based binder. The preparation method is as follows: diamond powder and copper-based binder are mixed for 0.5 hours, 10 grams of polyvinyl alcohol (1% of the mass of the mixture) is added to the mixture, stirred evenly and then granulated, the granulated mixture is spread in a crucible, loaded into a vacuum furnace (vacuum degree is lower than 133 Pa), heated in stages, debonded at 200°C for 15 minutes, and sintered at 800°C for 0.5 hours; 40-320 mesh sieves are used for screening and grading to obtain superhard aggregate abrasive with high bonding strength characteristics, and a stereoscopic microscope image of the obtained superhard aggregate abrasive grains is shown in Figure 1. The superhard aggregate abrasive grains are used to prepare resin-based consolidated abrasive pads for grinding K9 glass. The grinding pressure was 41 kPa, the grinding time was 40 min, the K9 glass material removal rate was 32 μm / min, the average surface roughness Ra was 157 nm, and the abrasive pad material removal rate changed by less than 6% during the machining process.
[0031] Comparative example 1.
[0032] like Figure 2 As shown. The difference between this comparative example and implementation 1 is that the brazing type metal binder is replaced by a ceramic binder, and the other parameters are the same. The SEM image of the obtained abrasive is shown in Figure 2. The abrasive is used to prepare a resin-based fixed abrasive pad for grinding K9 glass. The grinding pressure is 41kPa, the grinding time is 40min, the K9 glass material removal rate is 12μm / min, the average surface roughness Ra is 300nm, and the abrasive pad material removal rate changes less than 35% during the processing.
[0033] Example 2.
[0034] A superhard aggregate abrasive with high bonding strength characteristics is made of 500 grams of 15-30 μm cubic boron nitride powder and 500 grams of brazing type metal binder copper-based binder. The preparation method is as follows: the cubic boron nitride powder and the copper-based binder are mixed for 2 hours, 30 grams of polyvinyl acetate (3% of the mass of the mixture) is added to the mixture, stirred evenly and then granulated, the granulated mixture is spread in a crucible, loaded into a vacuum furnace (vacuum degree is lower than 133 Pa), heated in stages, debonded at 450°C for 60 minutes, and sintered at 900°C for 1.5 hours; a 100-200 mesh screen is used for screening and grading to obtain a superhard aggregate abrasive with high bonding strength characteristics. The superhard aggregate abrasive is used to prepare a resin-based fixed abrasive pad for grinding K9 glass. The grinding pressure was 41 kPa, the grinding time was 40 min, the K9 glass material removal rate was 28 μm / min, the average surface roughness Ra was 112 nm, and the abrasive pad material removal rate changed by less than 8% during the machining process.
[0035] Example 3.
[0036] A superhard aggregate abrasive with high bonding strength characteristics is made of 170 grams of 5-15 μm diamond powder and 30 silver-based metal binder of brazing type. The preparation method is as follows: diamond powder and silver-based metal binder are mixed in a mass percentage ratio of 17:3 for 6 hours, 30 grams of polyvinyl alcohol (15% of the mass of the mixture) is added to the mixture, stirred evenly and then granulated, the granulated mixture is spread in a crucible, loaded into a vacuum furnace (vacuum degree is less than 133 Pa), heated in stages, debonded at 350°C for 45 minutes, and sintered at 850°C for 2 hours; 80-320 mesh screen is used for screening and grading to obtain a superhard aggregate abrasive with high bonding strength characteristics. The superhard aggregate abrasive is used to prepare a resin-based consolidated abrasive pad for grinding sapphire crystals. The grinding pressure was 41 kPa, the grinding time was 40 min, the sapphire material removal rate was 2 μm / min, the average surface roughness Ra was 300 nm, and the abrasive pad material removal rate changed less than 5% during the machining process.
[0037] Example 4.
[0038] A superhard aggregate abrasive with high bonding strength characteristics is made of 400 grams of cubic boron nitride powder of 1 to 15 μm and 100 grams of brazing type metal binder nickel-based binder. The preparation method is as follows: cubic boron nitride and nickel-based metal binder are mixed for 8 hours, 50 grams of polyvinyl acetate (10% of the mass of the mixture) is added to the mixture, stirred evenly and then granulated, the granulated mixture is spread in a crucible, loaded into a vacuum furnace (vacuum degree is lower than 133 Pa), heated in stages, debonded at 600°C for 20 minutes, and sintered at 1000°C for 1 hour; 80 to 200 mesh screens are used for screening and grading to obtain a superhard aggregate abrasive with high bonding strength characteristics. The superhard aggregate abrasive is used to prepare a resin-based consolidated abrasive pad for grinding sapphire crystals. The grinding pressure was 41 kPa, the grinding time was 40 min, the sapphire material removal rate was 1.5 μm / min, the average surface roughness Ra was 235 nm, and the abrasive pad material removal rate changed by less than 6% during the machining process.
[0039] Example 5.
[0040] A superhard aggregate abrasive with high bonding strength characteristics is made of 700 grams of 10-15 μm diamond powder and 300 grams of brazing type copper-based metal binder. The preparation method is as follows: diamond powder and copper-based metal binder are mixed for 10 hours, 120 grams of polyvinyl acetate (12% of the mass of the mixture) is added to the mixture, stirred evenly and then granulated, the granulated mixture is spread in a crucible, loaded into a vacuum furnace (vacuum degree is lower than 133 Pa), heated in stages, debonded at 500°C for 30 minutes, and sintered at 920°C for 3 hours; sieving and grading with a 60-250 mesh sieve, a superhard aggregate abrasive with high bonding strength characteristics can be obtained. The superhard aggregate abrasive is used to prepare a ceramic-based consolidated abrasive pad for grinding silicon carbide. The grinding pressure was 41 kPa, the grinding time was 40 min, the silicon carbide material removal rate was 1.2 μm / min, the average surface roughness Ra was 263 nm, and the abrasive pad material removal rate changed less than 5% during the machining process.
[0041] Example 6.
[0042] A superhard aggregate abrasive with high bonding strength characteristics is made of 500 grams of diamond micropowder with a particle size of 10 to 30 μm and 500 grams of a brazing type metal binder (including copper-based, nickel-based and silver-based binders) with a particle size of 300 meshes. The preparation method is as follows: 500 grams of diamond micropowder and 200 grams of copper-based, 200 grams of nickel-based and 100 grams of silver-based metal binders are mixed in a mass percentage ratio of 5:2:2:1 for 12 hours, 60 grams of polyvinyl acetal (6% of the mass of the mixture) is added to the mixture, stirred evenly and then granulated, the granulated mixture is spread in a crucible, loaded into a vacuum furnace (vacuum degree is lower than 133 Pa), heated in stages, debonded at a medium temperature of 450°C for 50 minutes, and sintered at a high temperature of 950°C for 4 hours; 40 to 200 mesh sieves are used for screening and grading, so as to obtain the superhard aggregate abrasive with high bonding strength characteristics. The superhard aggregate abrasive grains were used to prepare a ceramic-based fixed abrasive pad for grinding silicon carbide. The grinding pressure was 41 kPa, the grinding time was 40 min, the silicon carbide material removal rate was 1.6 μm / min, the average surface roughness Ra was 300 nm, and the abrasive pad material removal rate changed by less than 5% during the machining process.
[0043] Example 7.
[0044] A superhard aggregate abrasive with high bonding strength characteristics is made of 850 grams of diamond micropowder with a particle size of 1 μm and 150 grams of brazing type metal binder copper-based binder with a particle size of 100 meshes. The preparation method is as follows: diamond micropowder and copper-based metal binder are mixed for 8.5 hours, 30 grams of polyvinyl acetate (3% of the mass of the mixture) is added to the mixture, stirred evenly and then granulated, the granulated mixture is spread in a crucible, loaded into a vacuum furnace (vacuum degree is lower than 133 Pa), heated in stages, debonded at 400°C for 35 minutes, and sintered at 980°C for 2 hours; sieved and graded using a 60-250 mesh sieve, and a superhard aggregate abrasive with high bonding strength characteristics can be obtained. The superhard aggregate abrasive is used to prepare a ceramic-based consolidated abrasive pad for grinding silicon carbide. The grinding pressure was 42 kPa, the grinding time was 45 min, the silicon carbide material removal rate was 1.3 μm / min, the average surface roughness Ra was 260 nm, and the abrasive pad material removal rate changed less than 4% during the machining process.
[0045] Example 8.
[0046] A superhard aggregate abrasive with high bonding strength characteristics is made of 600 grams of diamond micropowder with a particle size of 30 μm and 400 grams of brazing type metal binder nickel-based binder with a particle size of 300 meshes. The preparation method is as follows: diamond micropowder and nickel-based metal binder are mixed for 8 hours, 50 grams of polyvinyl acetate (5% of the mass of the mixture) is added to the mixture, stirred evenly and then granulated, the granulated mixture is spread in a crucible, loaded into a vacuum furnace (vacuum degree is lower than 133 Pa), heated in stages, debonded at 450°C for 35 minutes, and sintered at 900°C for 3.5 hours; 80-250 mesh screens are used for screening and grading to obtain superhard aggregate abrasive with high bonding strength characteristics. The superhard aggregate abrasive is used to prepare a ceramic-based consolidated abrasive pad for grinding silicon carbide. The grinding pressure was 40 kPa, the grinding time was 45 min, the silicon carbide material removal rate was 1.1 μm / min, the average surface roughness Ra was 268 nm, and the abrasive pad material removal rate changed less than 6% during the machining process.
[0047] Example 9.
[0048] A superhard aggregate abrasive with high bonding strength characteristics is made of 800 grams of diamond micropowder with a particle size of 15 μm and 200 grams of brazing type metal binder copper-based binder with a particle size of 1 mesh. The preparation method is as follows: diamond micropowder and copper-based metal binder are mixed for 12 hours, 10 grams of polyvinyl acetate (1% of the mass of the mixture) is added to the mixture, stirred evenly and then granulated, the granulated mixture is spread in a crucible, loaded into a vacuum furnace (vacuum degree is lower than 133 Pa), heated in stages, debonded at 600°C for 60 minutes, and sintered at 1000°C for 4 hours; sieved and graded using a 60-300 mesh sieve, and a superhard aggregate abrasive with high bonding strength characteristics can be obtained. The superhard aggregate abrasive is used to prepare a ceramic-based consolidated abrasive pad for grinding silicon carbide. The grinding pressure was 43 kPa, the grinding time was 35 min, the silicon carbide material removal rate was 1.4 μm / min, the average surface roughness Ra was 260 nm, and the abrasive pad material removal rate changed by less than 3% during the machining process.
[0049] The present invention does not involve parts that are the same as the prior art or can be implemented by using the prior art.
Claims
1. A superhard aggregate abrasive having high bonding strength characteristics, characterized in that: It consists of super-hard abrasive diamond or cubic boron nitride and brazing type metal binder. The mass percentage of super-hard abrasive diamond or cubic boron nitride is 50-85%, the mass percentage of brazing type metal binder is 15-50%, and the sum of all components is 100%.
2. The superhard aggregate abrasive grain according to claim 1, characterized in that: The brazing type metal binder is one or more combinations of copper-based alloys, nickel-based alloys or silver-based alloys, so that the superhard aggregate abrasive grains have high bonding strength and the abrasive grains will not break prematurely under greater pressure.
3. The superhard aggregate abrasive grain according to claim 1, characterized in that: The original particle size of the diamond abrasive grains or cubic boron nitride abrasive grains, that is, the primary particle size, is distributed between 1-30 μm.
4. The superhard aggregate abrasive grain according to claim 1, characterized in that: The brazing metal binder has a particle size of 1-300 meshes.
5. A method for preparing the superhard aggregate abrasive with high bonding strength characteristics as claimed in claim 1, characterized in that: The method comprises the following steps: (1) preparing super-hard abrasive grains and brazing-type metal binders in proportion and mixing them uniformly; (2) adding a binder to the mixed raw materials for granulation; (3) spreading the granulated mixture in a crucible, placing it in a vacuum furnace, heating it in stages, performing medium-temperature debonding and high-temperature sintering; and (4) performing screening and grading to obtain super-hard aggregate abrasive grains with high bonding strength characteristics.
6. The preparation method according to claim 5, characterized in that: The mixing method in step (1) is dry mixing, and the mixing time is 0.5-12 hours.
7. The preparation method according to claim 5, characterized in that: In the step (2), the binder is a mixture of one or more of polyvinyl alcohol, polyvinyl acetate and polyvinyl acetal, and the content thereof is 1% to 15% of the mass of the mixed raw materials.
8. The preparation method according to claim 5, characterized in that: In the step (3), the medium-temperature debonding temperature is 200-600°C, the debonding time is 0.25-1 hour, and the vacuum degree of the vacuum furnace is controlled to be lower than 133 Pa; the sintering temperature should be controlled between 800-1000°C according to the type and proportion of the brazing metal binder, the sintering time is 0.5-4 hours, and the vacuum degree of the vacuum furnace is controlled to be lower than 133 Pa.
9. The preparation method according to claim 5, characterized in that: In the step (4), the sintered abrasive particles are sieved using a 40-320 mesh sieve.
10. The superhard aggregate abrasive grain according to claim 1, characterized in that: It is used for preparing resin-based or ceramic-based superhard abrasive tools, which include grinding wheels, blades, grinding discs, polishing discs and honing heads used in precision grinding, cutting, grinding, polishing and honing.
Citation Information
Patent Citations
Composite abrasive particle with abrasive particle / nickel oxide core-shell structure, and preparation method and application thereof
CN102719219B
A composite abrasive with an abrasive / alumina core-shell structure, its preparation method and application
CN102719220B
A method for preparing a self-sharpening sintered abrasive and its uses
CN105856078B
Honing stone as well as preparation and application thereof
CN103182672A
Production method of polycrystalline cubic boron nitride grinding material
CN106905922A